O Rock chegou à cidade: as transformações na noite Lisboeta da década de 80 - MArtins, Ana (2018)
The 80th decade saw the emergence of the portuguese rock music boom and the city of Lisbon was the privileged stage to receive the first transformations in the youth ways of living. Rock Rendez vous and Frágil were two of the spaces more emblematic of the decade, both in the dissemination of music bands and in the leisures' transformations.